Fiber consumption effect on non-communicable disease: how big is the impact? - Yuli Indarti (Qanun Medika - Jurnal Kedokteran FK UMSurabaya, 2020)
Abstract  Non-communicable diseases have effects on the quality of human resources because, in addition to causes of death and morbidity, they also reduce productivity. Fiber intake was allegedly affecting the incidence of non-communicable diseases. The purpose of this literature review is to look at the link between fiber intake and the incidence of non-communicable diseases and the effect of fiber supplements to treat non-communicable diseases. Several literature indicate that fiber intake is associated with cardiovascular disease, diabetes mellitus, cancer, and obesity. Research also shows fiber supplementation can improve metabolic profiles, blood sugar, insulin resistance in cardiovascular and diabetes mellitus patients. Fiber supplementation also reduces the risk of breast cancer. Fiber intake is related to the incidence of non-communicable diseases and can overcome some non-communicable diseases Keywords             : fiber, cardiovascular disease, diabetes mellitus, cancer, supplement